Strategi Pemasaran Pada Produk Simpanan Haji KSPPS Mitra Usaha Ideal Jawa Timur Cabang Sekapuk Gresik - Irdatul Wardah; Nurul Istifadhoh; Wiwik Saidatur Rolianah (JES (Jurnal Ekonomi Syariah), 2021)
Abstract: In applying marketing strategy, the subjects or sellers must be able to educate the customers about the product superiority with integrity. They do not need to lie or deceive the clients in order to get the profit. They even need to be the good and professional communicator. The changing number of members in KSPPS Mitra Usaha Ideal Sekapuk, East Java, needs a further analysis to determine the marketing strategy in order to keep surviving in financial industry. This research applies qualitative approach in conformity with field research to obtain the data that are in correlation with the latest social condition and environment. The research findings on the marketing strategy of products of hajj savings in KSSPS Mitra Usaha Ideal Sekapuk, East Java, generate the application of marketing strategy through segmentation, targeting, and positioning by rising door to door strategy. Keywords: strategy; marketing; hajj savings